Earth resources (Manila : P. Leyco, 1980)
A selection of annotated references to unclassified reports and journal articles that were introduced into the NASA scientific and technical information system and announced in Scientific and technical aerospace reports (STAR) and International Aerospace Abstracts (IAA).
Also issued online.
Vols. for 19 -Apr. 1978 issued by the Scientific and Technical Information Office; Aug. 1978-19 by the Scientific and Technical Information Branch; <Feb. 1989-> by the Scientific and Technical Information Division.
Vols. for 19 -19 prepared by the NASA Scientific and Technical Information Facility.
Description based on: Issue 20 (Jan. 1979).
SERBIB/SERLOC merged record
Keywords: Astronautics in earth sciences -- Bibliography -- Periodicals; Earth sciences -- Bibliography -- Periodicals; Remote sensing -- Bibliography -- Periodicals; Geology; Engineering; Astronautics in earth sciences; Earth sciences; Remote sensing; Periodicals; Bibliography; Periodicals